Berbagi Sayuran dari Pohon Agroforestri untuk Membantu Meringankan Warga Binaan LKS Anhaarun - Rawana Rawana (Humanism: Journal of Community Empowerment (HJCE), 2022)
The COVID-19 pandemic has spread massively in various corners of the country with various variants, having a significant impact on various aspects of life, both health and economic aspects. Residents assisted by the Social Welfare Institution (SWI) Anhaarun Yogyakarta are poor and orphans and most of them are widows so they really need help to meet their daily needs, including vegetables. The purpose of the service is to provide vegetable ingredients derived from agroforestry system trees to help alleviate the vegetable needs of the perishing residents of SWI Anhaarun Yogyakarta. The service was carried out in the assisted residents of SWI Anhaarun in Keparakan Village, Mergangsan District, Yogyakarta City. The service method was carried out by distributing vegetables from agroforestry trees by making packages of lodeh jackfruit and lodeh kluwih vegetables put in plastic bags, equipped with plastic bags and side dishes. A total of 100 packages, which were divided into two locations, namely the homes of Mrs. Dian and Mrs. Bambang, each with 50 packages. The conclusions of this activity were (1) the people of Keparakan Kidul village-like jackfruit (gori) (Artocarpus heterophyllus), kluwih (Artocarpus camansi) and melinjo (Gnetum gnemon) vegetables during the covid-19 pandemic, (2) vegetables harvested from agroforestry area have helped to solve the problems of SWI Anhaarun members.  Keywords:  Agroforestry, pandemic, vegetables